2019
DOI: 10.1111/jcmm.14635
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from pro‐inflammatory bone marrow‐derived mesenchymal stem cells reduce inflammation and myocardial injury via mediating macrophage polarization

Abstract: Exosomes are served as substitutes for stem cell therapy, playing important roles in mediating heart repair during myocardial infarction injury. Evidence have indicated that lipopolysaccharide (LPS) pre‐conditioning bone marrow‐derived mesenchymal stem cells (BMSCs) and their secreted exosomes promote macrophage polarization and tissue repair in several inflammation diseases; however, it has not been fully elucidated in myocardial infarction (MI). This study aimed to investigate whether LPS‐primed BMSC‐derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
148
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(163 citation statements)
references
References 61 publications
3
148
2
Order By: Relevance
“…Compared with MSC-EVs, LPS-primed MSC-EVs elevated phosphorylation activation of AKT1 and M2 polarization in vitro, while inhibiting phosphorylation of AKT2 and M1 polarization. The effect of LPS-primed MSC-EVs on macrophage polarization was partially abolished with either knocking down of AKT1 and AKT2, indicating the role of AKT1/AKT2 signaling pathway on macrophage polarization [78]. In a doxorubicin-induced dilated cardiomyopathy model, mice received bone marrow-derived MSC-EVs improved cardiac function, alleviated cardiac dilation, and attenuated cardiomyocytes apoptosis.…”
Section: Msc-ev-mediated Macrophage Polarization In Cardiovascular DImentioning
confidence: 97%
“…Compared with MSC-EVs, LPS-primed MSC-EVs elevated phosphorylation activation of AKT1 and M2 polarization in vitro, while inhibiting phosphorylation of AKT2 and M1 polarization. The effect of LPS-primed MSC-EVs on macrophage polarization was partially abolished with either knocking down of AKT1 and AKT2, indicating the role of AKT1/AKT2 signaling pathway on macrophage polarization [78]. In a doxorubicin-induced dilated cardiomyopathy model, mice received bone marrow-derived MSC-EVs improved cardiac function, alleviated cardiac dilation, and attenuated cardiomyocytes apoptosis.…”
Section: Msc-ev-mediated Macrophage Polarization In Cardiovascular DImentioning
confidence: 97%
“…Recent studies have shown that MSC-based treatment of ischemia-induced cardiac damage can be mediated through the secretion of exosomes [5][6][7][8][9]. MSC-secreted exosomes have been reported to exert an anti-apoptotic effect on CMCs both in vivo and in vitro [5][6][7]10].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has also shown that culturing macrophages with exosomes from LPS-primed MSCs increases STAT3 gene expression, secretion of cytokines (IL-10 and IL-15), and expression of growth factors (FLT-3L); such macrophages also extend survival in a mouse model of acute radiation syndrome [122]. A different study showed that exosomes from LPS-primed MSCs increased M2 macrophage polarization, resulting in the attenuation of post-infarction inflammation and cardiomyocyte apoptosis in a mouse model of MI [123].…”
Section: Pre-conditioning Of Mscs With Biomolecules or Chemicalsmentioning
confidence: 99%